ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Budidarma, I Gusti Agung Musa; Suak, Yonathan Andrew (JBE (Journal of Business and Economics), 2013)
This study seeks to find out which factors are affecting stock price of manufacturing companies listed in Indonesian Stock Exchange (IDX).The sample of this study are companies in manufacturing sectors that paid dividend regularly and listed in IDX for the period of 2009 to 2011. Simple regression analysis and moderate regression analysis are used in this study. The findings indicate that profitability, liquidity, managerial ownership, and debt policy partially is not affecting stock price. In addition, the dividend as a moderate variable is unable to significantly moderate the effect of liquidity, managerial ownership, and debt policy toward stock price. However, the dividend as a moderate variable is able to significantly moderate the effect of profitability toward stock price.